Identification and validation of signature for prognosis and immune microenvironment in gastric cancer based on m6A demethylase ALKBH5 - Ji, Tiannan; Gao, Xiaohui; Li, Dan; Huai, Siyuan; Chi, Yajing; An, Xian; Ji, Wenyu; Yang, Siming; Li, Jianxiong (Frontiers in Oncology, 2023)
Background: N6-methyladenosine (m6A) RNA regulators play important roles in cancers, but the functions and mechanism of them have not been demonstrated clearly in gastric cancer (GC). Methods: In this study, the GC samples with clinical information and RNA transcriptome were downloaded from TCGA (The Cancer Genome Atlas) database. The different expression genes were compared by absolute value and median ± standard deviation (sd). Samples with complete information were randomly divided into a training dataset and a test dataset. The differential expression genes (DEGs) between ALKBH5-low and ALKBH5-high subgroups were identified in training dataset and constructed a risk model by Cox and LASSO regression. The model was testified in test datasets, the overall survival (OS) was compared with Kaplan-Meier method and immune cell infiltration was calculated by CIBERSORT algorithm in the low-risk and high-risk subgroups based on the model. ALKBH5’s protein levels were detected with immunohistochemistry (IHC). Relative expression of mRNA was detected with quantitative PCR (Polymerase Chain Reaction). Results: ALKBH5 was the only regulator whose expression was lower in tumor samples than that in normal samples. Low expression of ALKBH5 led to poor overall survival of GC patients and seemed to be an independent protective factor. The model based on ALKBH5-regulated genes was validated in both datasets (training/test) and displayed a potential capacity to predict clinical prognosis. Gene Ontology (GO) analysis implied that the DEGs were involved in immune response, CIBERSORT results indicated that ALKBH5 and its related genes could alter the immune microenvironment of GC. The protein levels of ALKBH5 were verified as lowly expressed in GC tissues. SLC7A2 and CGB3 were down-regulated with ALKBH5 knockdown. Conclusions: In this study, we found that ALKBH5 might be a suppressor of GC, ALKBH5 and its related genes were latent biomarkers and immunotherapy targets.